Fission studies in inverse kinematics with the R3B setup - Graña-González A.; Rodríguez-Sánchez J.L.; Benlliure J.; García-Jiménez G.; Alvarez-Pol H.; Cortina-Gil D.; Atar L.; Audouin L.; Authelet G.; Besteiro A.; Blanchon G.; Boretzky K.; et al. (EPJ Web of Conferences, 2023)
Nuclear fission is a complex dynamical process, whose description involves the coupling between intrinsic and collective degrees of freedom, as well as different quantum-mechanical phenomena. For this reason, to this day it still lacks a satisfactory and complete microscopic description. In addition to the importance of describing fission itself, studies of the r-process in astrophysics depend on fission observables to constrain the theoretical models that explain the isotopic abundances in the Universe. To improve on the existing data, fission reactions of heavy nuclei in inverse kinematics are produced in quasi-free (p,2p) scattering reactions, which induce fission through particle-hole excitations that can range from few to tens of MeV. In order to study the evolution of the fission yields with temperature, the excitation energy of the fissioning system must be reconstructed, which is possible by measuring the four-momenta of the two outgoing protons. Performing this kind of experiment requires a complex experimental setup, providing full isotopic identification of both fission fragments and an accurate measurement of the momenta of the two outgoing protons. This was realized recently at the GSI/FAIR facility and some of the results obtained for the charge distributions are presented in this work.